Trade-off between productivity and environmental sustainability in irrigated vs. rainfed wheat production in Iran. (10th February 2018) - Tahmasebi, Maryam; Feike, Til; Soltani, Afshin; Ramroudi, Mahmoud; Ha, Nan
Abstract: Wheat is a strategic crop for Iran with respect to food security and environmental impact. In the northeastern Golestan Province irrigated and rainfed wheat production systems co-exist. In the light of climate change the comparative assessment of the two systems regarding productivity and sustainability is of urgent importance. This paper aims to contribute to a more informed debate on the viability of irrigation in marginal crop production regions. For this purpose, the present study investigates productivity and environmental impact of 540 wheat producing farm households (259 irrigated; 281 rainfed) in Golestan by partial life cycle assessment (LCA) methodology using greenhouse gas (GHG) emissions and product carbon footprint (PCF) as environmental sustainability indicators. The study finds huge heterogeneity among wheat producers with regard to yield, GHG emissions and PCF. Comparing irrigated and rainfed production showed that irrigation in average leads to 22% higher yields. However, the environmental impact of irrigated production is disproportionally high leading to 110% higher GHG emissions and 62% higher PCF, which highlights the trade-off between productivity and environmental sustainability. The major contributors to total GHG emissions of wheat production are energy for irrigation (only in irrigated production), N2 O emissions related to fertilization and residue handling, diesel for machinery, and emissions related to fertilizer production and transport. Increased GHG emissions and PCF in irrigated compared to rainfed production are not only attributed to the energy required for irrigation, but also to increased fertilizer and other production inputs. Splitting the farmers into high, medium and low yield groups indicates the potential for increasing yields through increased input intensity without negative effects on PCF. The study's results demonstrate the potential of better balancing the trade-offs between productivity and sustainability of wheat production in marginal wheat production regions of the world. Highlights: Co-existing irrigated and rainfed wheat production systems are analyzed. Primary wheat production data of 540 wheat producers is assessed. Irrigation increases yields by 22% but GHG emissions by 110%. High yield farmers have lower product carbon footprint than low yield farmers. The viability of irrigation is questionable under increasing water competition.